Ratio Legis System Law Related Child Criminal Justice Qualification Of Criminal Sanctions And Actions - Fransiska Novita Eleanora; Widya Romasindah Aidy (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
The formation of a regulation aims to be able to regulate and also be able to organize the existence of life in a country where in the life of a society that is also regulated by the law to be able to obtain certainty, as well as benefits and also justice in life in the state. It also includes regulations concerning criminal justice for children in conflict with the law or commonly referred to as children as perpetrators of criminal acts, where children, even as perpetrators, must pay attention to their human rights while in the Special Child Development Institution (LPKA) and the law implies there are criminal sanctions that contain the main and additional punishments that will be imposed on children, but in the birth of the SPPA law it has not explained which criminal acts are in the form of violations and crimes, regardless of the age limit of the child, at least the classification between violations and crimes should be included in the law on the juvenile justice system because it is related to child protection because basically punishment is the last resort imposed on children when the settlement of diversion does not reach an agreement between the perpetrator and the victim, what is the legal ratio in the formation of the law on the juvenile justice system without including any classification of violations and crimes committed by children.